Perioperative multimodal analgesia in orthopedic and trauma patients for minimal invasive surgical intervention - Buryanov, Oleksandr; Sobolevskiy, Yuriy; Omelchenko, Taras; Babochkin, Ruslan; Andreeva, Mariya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The goal: to evaluate the effectiveness of the proposed method of perioperative multimodal analgesia with complex use of non-opioid analgesics only of central and peripheral actions during minimally invasive surgical procedures compared with the conventional scheme of multimodal analgesia using opiate analgesics and adjuvant preparations. The methods: patients aged from 18 to 65 years (33.6 years) were divided into two groups. Main group (89 patients): non-narcotic analgesics of central and peripheral actions (dexketoprofen and paracetamol) were used in the complex multimodal analgesia. Comparison group (61 patients): opioid analgesics (Promedolum) were used. Efficacy was assessed after recovery of active movements and sensitivity in lower extremities (on average 4 hours after spinal anesthesia) using following criteria: pain intensity on a visual analogue scale before and 1 and 6 hours after the administration of analgesic, required total duration of anesthesia, the mean duration of analgesia, the effect of the drug on the patient’s state of health and occurrence of side effects. Results: it was shown that the rate of occurrence of analgesia in both groups had no differences, but its duration in the study group was higher — (8.1 ± 1.9) h against (5.7 ± 1.6) h in the comparison group. This fact proves prolonging effect of the analgesic action of the combination of paracetamol and dexketoprofen. The absence of side effects typical for opioids in the main group was proved, but in comparison group these side effectes were observed in almost every fifth patient. The average duration of use of painkillers was also different. The need for analgesics in the main group of patients was in the range (3.2 ± 1.0) days, and it was higher in the control group (4.3 ± 1.9) days.